Praktik Income Smoothing dan Potensi Displaced Commercial Risk Pada Sukuk Mudharabah - Brahim, Singgih Rasyitu; Muhammad, Rifqi (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2020)
This paper aims to discuss the implementation of one of the mudharabah sukuk issued by corporations. Furthermore, the paper specifically discusses indications of Income Smoothing practices and the potential for Displaced Commercial Risk (DCR) in the implementation of sukuk with mudharabah contracts.Â  The type of research uses qualitative methods in the form of library research with a descriptive approach. This paper reveals the fact that there is a practice of Income Smoothing in the distribution of profit sharing to investors in Sukuk Mudharabah PT SMI. On the other hand, mudharabah sukuk also has DCR potential that will be experienced by investors because the nature of the investment is not classified as sufficiently liquid compared to other investment models and has a relatively high risk. Therefore, a special scheme and regulations are needed for sukuk mudaraba in terms of overcoming the problem of income smoothing and preventing the occurrence of DCR.